Correlations of water iodine concentration to earlier goitre frequency in Sweden-an iodine sufficient country with long-term iodination of table salt - Sofia Manousou; Maja Stål; Robert Eggertsen; Michael Hoppe; Lena Hulthén; Helena Filipsson Nyström (Komiyama Printing Co. Ltd, 2019)
Abstract Background Before iodination of Swedish table salt in 1936, iodine deficiency resulting in goitre and hypothyroidism was common. Sweden has become iodine sufficient, as shown in a national survey in 2007, proving its iodination fortification programme effective for the general population. The objective of this study was to collect drinking water from water treatment plants nationally and test if water iodine concentration (WIC) correlated to urinary iodine concentration (UIC) of school-aged children in a national survey 2007 to former goitre frequency in 1929 and to thyroid volume data in 2007. Methods In 2012, 166 treatment plants, located in 57% (166 of 290) of all Swedish municipalities, were asked to collect drinking water samples of approximately 10 ml. In 2007, tap water samples of the same volume were collected from 30 randomly selected schools for the national survey. Analysis of WIC was done in both treatment plants in 2012 (n = 166) and tap water in 2007 (n = 30). The correlation of WIC to the children's UIC and thyroid volume after iodination was tested based on data from the national survey in 2007. The association of WIC to former goitre frequency was tested based on pre-iodination data, derived from a map of goitre frequency drawn in 1929. Results The median WIC from water treatment plants was 4.0 μg/L (range 0-27 μg/L). WIC was similar in coastal and inland areas, for both ground and surface water. WIC correlated with historical goitre areas and was lower in the goitre areas than in non-goitre areas (p < 0.001). WIC in the same municipalities as the schools correlated with the UIC of children (p < 0.01), but not with their thyroid volume. Conclusions WIC still contributes to iodine nutrition in Sweden, but iodination overrides the goitre effect.